2022
DOI: 10.3390/nu14235021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Diabetic Retinopathy: A Systematic Review of the Literature

Abstract: Diabetic retinopathy (DR) is a common microvascular complication of diabetes mellitus. The evidence connecting dietary intake and DR is emerging, but uncertain. We conducted a systematic review to comprehensively summarize the current understanding of the associations between dietary consumption, DR and diabetic macular edema (DME). We systematically searched PubMed, Embase, Medline, and the Cochrane Central Register of Controlled Trials between January 1967 to May 2022 for all studies investigating the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 104 publications
0
28
0
Order By: Relevance
“…Karatzi K found that caffeine consumption was associated with wider retinal venular calibre, but no association was found between caffeinated drinks (coffee and tea) and retinal vessel calibres [22]. A systematic review revealed the uncertain effect of caffeine on the retina [7]. Because of the complexity and di culty of implementing an observational study in the real world, the conclusion may be disturbed by unknown confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karatzi K found that caffeine consumption was associated with wider retinal venular calibre, but no association was found between caffeinated drinks (coffee and tea) and retinal vessel calibres [22]. A systematic review revealed the uncertain effect of caffeine on the retina [7]. Because of the complexity and di culty of implementing an observational study in the real world, the conclusion may be disturbed by unknown confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study found that coffee consumption may be associated with a reduced risk of DR [4], while in another cross-sectional study, no signi cant association between coffee intake and DR was found [5]. In addition, most prospective cohort and case-control studies did not nd a signi cant association between alcohol intake and retinopathy [6,7], but Giuffrè G proved the protective effect of alcohol on DR over a long period. Evidence has shown the protective role of tea for DR, and Horikawa C and Yan X reported no statistically signi cant result between juice or milk intake and the incidence of DR [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Protective effects on DR from consumption of fruit, vegetables, fiber, fish, tea, oleic acid, and Mediterranean diet ( Shah et al, 2022 ). For example, a high-fiber diet may enhance the serum metabolic level of T2DM patients by altering the GM flora ( Chen et al, 2023 ).…”
Section: The Potential Treatment For Dr: Regulation Of the Gut Microe...mentioning
confidence: 99%
“…Many researchers have explored new treatment options for DR. New aspects of therapeutic research currently underway include mediators of the angiopoietin signaling axis, immunosuppressants, nonsteroidal anti-inflammatory drugs (NSAIDs), inhibitors of oxidative stress, and inhibitors of viral viscosity (VVIs) [ 8 , 37 ]. Moreover, diet is also closely related to DR, and diets including fruits and vegetables can have a protective effect on DR [ 38 ].…”
Section: Introductionmentioning
confidence: 99%